ANALISIS KIMIA BEBERAPA JENIS KAYU INDONESIA - Gustan Pari; Fityani B Lestari (Jurnal Penelitian Hasil Hutan, 1990)
Chemical  analyses of  several  Indonesia wood  from West  Java and  Kalimantan   has been conducted. The chemical component tested  consisted  of  holocellulose, cellulose,  lignin, pentosan, ash and silica content, solubility in cold water, hot water, one percent  sodium  hydroxide and alcohol benzene  extractrive.The result  shows  that  the holocellulose content ranges from 57,95 - 61,97 percent,    cellulose  from  40,93 - 57,41 percent, lignin  from 22,01 - 29,00  percent, pentosan from  8,35-21,50  percent, ash content  from  0,18 - 3,64 percent, silica  content from  0,05 - 2,47  percent. The  solubility  in cold  water  ranges from  0,39  -   3,59  percent, hot  water  from 0,56  - 9,48  percent, in  one  percent sodium hydroxide  from   6,25  - 31,68 percent and  in alcohol  benzene  (1:2) from 0,95  -  6,03 percent.